The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1071/bt00094
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA phylogeography of Eucalyptus globulus

Abstract: The pattern of variability in chloroplast DNA (cpDNA) of Eucalyptus globulus Labill. (Myrtaceae) was studied using 270 samples from southern Australia. Forty variable sequence characters were found, defining 105 haplotypes. Haplotypes were assigned to three major cpDNA clades based on their phylogeny. The pattern of cpDNA variation did not conform to subspecies boundaries; however, there was a strong geographic structure to the distribution of clades and haplotypes. One clade (JC) was geographically central an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
104
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 42 publications
5
104
0
Order By: Relevance
“…Analysis of the extended hypervariable sequence, termed J LA + (Freeman et al 2001), found the distribution of major haplotype clades to be broadly consistent with that in the former study of E. globulus (Jackson et al 1999), but allowed for a greater resolution of the phylogenetic relationships between and within haplotype clades. A continental Australian origin of E. globulus was supported by the widespread distribution of the basal J Cg haplotypes on continental Australia.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…Analysis of the extended hypervariable sequence, termed J LA + (Freeman et al 2001), found the distribution of major haplotype clades to be broadly consistent with that in the former study of E. globulus (Jackson et al 1999), but allowed for a greater resolution of the phylogenetic relationships between and within haplotype clades. A continental Australian origin of E. globulus was supported by the widespread distribution of the basal J Cg haplotypes on continental Australia.…”
Section: Introductionmentioning
confidence: 60%
“…A continental Australian origin of E. globulus was supported by the widespread distribution of the basal J Cg haplotypes on continental Australia. There was also evidence of glacial refugia in the coastal areas of eastern and south-eastern Tasmania, with the most recent seed migration of E. globulus between Tasmania and continental Australia occurring along a western island migration route during a glacial maximum and accompanying reduced sea level (Freeman et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations